2006
DOI: 10.1158/1535-7163.mct-05-0428
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations associated with acquired temozolomide resistance in SNB-19, a human glioma cell line

Abstract: Gliomas are highly lethal neoplasms that cannot be cured by currently available therapies. Temozolomide is a recently introduced alkylating agent that has yielded a significant benefit in the treatment of high-grade gliomas. However, either de novo or acquired chemoresistance occurs frequently and has been attributed to increased levels of O 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 50 publications
6
43
0
Order By: Relevance
“…In our data, methylation status of the promoter region was not changed (fully methylated in both U251Wt and U251R cells), suggesting that MGMT expression is not involved in the acquired TMZ resistance in GBM. This is consistent with a previous report by Auger et al [33] in which SNB-19 glioma cells and their resistant variants were used. Other mechanism may be involved in the step of obtaining the resistance.…”
Section: Discussionsupporting
confidence: 93%
“…In our data, methylation status of the promoter region was not changed (fully methylated in both U251Wt and U251R cells), suggesting that MGMT expression is not involved in the acquired TMZ resistance in GBM. This is consistent with a previous report by Auger et al [33] in which SNB-19 glioma cells and their resistant variants were used. Other mechanism may be involved in the step of obtaining the resistance.…”
Section: Discussionsupporting
confidence: 93%
“…As a DNA repair enzyme, MGMT is a protein that can transfer the alkylated group of methylguanine from the O 6 position to its own cysteine residue (4,5,15), so that the TMZ-induced guanine damage in DNA can be repaired. Previous studies have demonstrated that the levels of MGMT vary considerably in glioma cells, which can be divided into the MGMT repair-deficient cells and cells with a sufficient MGMT repair (16).…”
Section: Discussionmentioning
confidence: 99%
“…Although maximal surgical resection combined with TMZ therapy and irradiation has significantly improved the quality of life and prolonged the survival time of patients with GBM, the overall clinical prognosis remains unsatisfactory due to intrinsic or acquired tumor cell resistance to TMZ (3). Previous studies have demonstrated that O 6 -methylguanine-DNA methyltransferase (MGMT) is the main factor responsible for chemoresistance to TMZ in GBM cells (4,5). However, the molecular mechanism of TMZ resistance is more complex than a simple dependence on MGMT expression.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, defective DNA MMR can result in tolerance to TMZ regardless of MGMT activity and continuance of DNA replication (4,5). However, some studies have demonstrated resistance to TMZ that was independent of such candidates, suggesting that other major mechanisms were involved in the resistance to TMZ (4,6). Furthermore, tumor chemotherapy resistance may be very complicated, often multifactorial and with many genes involved.…”
Section: Introductionmentioning
confidence: 99%